Panorama of neoplasms of upper GI tract: a 5 year research study - Kumar, T.C.S. Suman; Babu, P. Venkata Ramana; Reddy, E. Sudhakar; Anuradha, B.; Saiprasad, B.V.; Naik, V. Siva Sankara; Kavitha, K.; Swarnabala, M. (International Journal of Research in Medical Sciences, 2017)
Background: The diseases of the gastrointestinal tract (GIT) are the most common and leading cause of morbidity and mortality than the disorders of any other systems of the body. Gastrointestinal (GI) tract tumors are one of the most common cancers accounting for 11% of all cancers. Among these tumors, upper gastrointestinal tract malignancies are quite aggressive with a dismal prognosis. Malignant tumors are most common than benign. The most common carcinoma of the esophagus is Squamous cell carcinoma (SCC). Incidence of SCC is less than 5 per 100,000 populations in males and 1 per 100,000 populations in females. Gastric cancer was the second most common cancer in the World and 60% of them occurred in developing countries. The most common carcinoma of the Stomach is Adenocarcinoma. Aim & Objectives: To study the spectrum of neoplastic lesions of the upper gastrointestinal tract by the examination of endoscopic biopsies and surgically resected specimens. To determine the degree of severity of the malignancies by assessing the depth of invasion, Lymph nodal & Omental spread. Methods: The present study is both retrospective & prospective study for a period of 5 years from January 2007 to December 2011. The sample size includes all the endoscopic biopsies & surgically resected specimens of gastrointestinal tract received at Department of Pathology, S.V. Medical College, Tirupati. The study also obtained clearance from the ethical committee of the institution. The biopsy specimens thus obtained were fixed in 10% buffered neutral formalin. The sections were stained routinely with H & E. Special stains and IHC done wherever necessary. Results: we have received 120 specimens regarding the upper gastrointestinal system. Among these 120 specimens, 71 specimens were endoscopic biopsies & 49 specimens were surgically resected specimens. Out of 71 Endoscopic biopsies 28 biopsies were malignant among which 2 was esophagus and 26 were stomach. Out of 49 surgically resected specimens 1 was benign and 32 were malignant tumors. Out of 59 neoplasms of stomach there were single cases each of Sub mucosal Lipoma, Malignant lymphoma, GIST & 56 cases of Adenocarcinoma & its variants were noted. Conclusion: Most of the neoplasms are of stomach (97%). All the neoplasms are malignant except one benign lesion sub mucous lipoma of stomach. Most of the neoplasms of stomach were Adenocarcinoma (96.5%). Both tumors of esophagus were squamous cell carcinoma occurred after 50 years of age.